Factors Affecting Generation Z's Intention To Pay Zakat Through Digital Payment - Wahrudin, Bambang; Purwaningrum, Titis; Nurhayati, Anna; Setiawan, Fery (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2024)
This study aims to analyze the effect of performance expectancy, effort expectancy, social influence, facilitating condition, and price value on the intention of Generation Z to pay zakat through digital payments. This study uses a descriptive quantitative method. The population of this study is Generation Z Ponorogo, who have paid zakat through digital payments, where the number is still being determined. Accidentally, sampling was used and measured using the Hair approach so that 98 respondents were obtained. The data source for this study uses primary data obtained from respondents filling out questionnaires, which are then analyzed using multiple linear regression assisted by SPSS 25 software. The study results indicate that facilitating conditions and price value positively affect the intention of Generation Z to pay zakat through digital payments. However, performance expectancy, effort expectancy, and social influence do not affect Generation Z's intention to pay for zakat through digital payments. The results of this study can complement existing theories, especially the effect of facilitating conditions and price value on intention. The results of this study can be used as a reference for zakat management institutions to increase the intention of the community, especially Generation Z, to pay for zakat through digital payments.